Serviceology for Services : 7th International Conference, ICServ 2020, Osaka, Japan, March 13–15, 2020, Proceedings /: 7th International Conference, ICServ 2020, Osaka, Japan, March 13–15, 2020, Proceedings. (2020) - Unknown
No abstract available